HbA1c as a prognostic indicator in prediabetics with acute coronary syndrome - Gadwalkar, Arathi S.; K., Prabhakar; A., Raveesha; Ghungroo, Shaama (International Journal of Research in Medical Sciences, 2020)
Background: The role of HbA1C in predicting the outcomes of acute coronary syndrome remains controversial. Lesser is known about it in non-diabetic patients. Therefore authors conducted a study to seek association between the HbA1C levels and the clinical outcome in non-diabetic patients who presented with acute coronary syndrome. Objective of the study was to estimate HbA1C levels in population of prediabetics and non-diabetics and to document and correlate major adverse cardiac events in prediabetic and non-diabetics. Method: This case control study included consecutive patients (n=68) without known diabetes mellitus admitted with acute coronary syndrome (STEMI, NSTEMI, UA) at our hospital. HbA1c was measured on admission. The patients were divided into 2 groups according to their HbA1c level (group 1 HbA1c<5.7%, group 2 HbA1c>5.7%). The main outcome was MACE (major adverse cardiac events including cardiogenic shock, arrhythmia, heart failure). Results: There was no significant difference between baseline characteristics of both groups but complications were seen in higher number cases with HbA1c >5.7%. No significant difference in mortality was found. On analysis HbA1c >5.7% was found to be an independent predictor of MACE. Conclusion: HbA1C is a predictor of major adverse cardiac events. Measurement of HbA1C levels may improve risk assessment in such patients presenting with ACS.